"Happiness Inventors": Informing Positive Computing Technologies Through Participatory Design With Children. - Yarosh, Svetlana; Schueller, Stephen Matthew (Journal of Medical Internet Research, 2017)
Background: Positive psychological interventions for children have typically focused on direct adaptations of interventions developed for adults. As the community moves toward designing positive computing technologies to support child well-being, it is important to use a more participatory process that directly engages children's voices.Objective: Our objectives were, through a participatory design study, to understand children's interpretations of positive psychology concepts, as well as their perspectives on technologies that are best suited to enhance their engagement with practice of well-being skills.Methods: We addressed these questions through a content analysis of 434 design ideas, 51 sketches, and 8 prototype and videos, which emerged from a 14-session cooperative inquiry study with 12 child "happiness inventors." The study was part of a summer learning camp held at the children's middle school, which focused on teaching the invention process, teaching well-being skills drawn from positive psychology and related areas (gratitude, mindfulness, and problem solving), and iterating design ideas for technologies to support these skills.Results: The children's ideas and prototypes revealed specific facets of how they interpreted gratitude (as thanking, being positive, and doing good things), mindfulness (as externally representing thought and emotions, controlling those thoughts and emotions, getting through unpleasant things, and avoiding forgetting something), and problem solving (as preventing bad decisions, seeking alternative solutions, and not dwelling on unproductive thoughts). This process also revealed that children emphasized particular technologies in their solutions. While desktop or laptop solutions were notably lacking, other ideas were roughly evenly distributed between mobile apps and embodied computing technologies (toys, wearables, etc). We also report on desired functionalities and approaches to engagement in the children's ideas, such as a notable emphasis on representing and responding to internal states.Conclusions: Our findings point to promising directions for the design of positive computing technologies targeted at children, with particular emphases on the perspectives, technologies, engagement approaches, and functionalities that appealed to the children in our study. The dual focus of the study on teaching skills while designing technologies is a novel methodology in the design of positive computing technologies intended to increase child well-being.